Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) \(x^2+4x+4=\left(x+2\right)^2\)
b) \(x^2-8x+16=\left(x-4\right)^2\)
c) \(\left(x+5\right)\left(x-5\right)=x^2-25\)
g) \(\left(x-2\right)\left(x^2-2x+4\right)\)
\(=x^3-8\)
1: =(4x-1)^2-3(4x-1)
=(4x-1)(4x-1-3)
=4(x-1)(4x-1)
2: =-8x^4y^5(2y+3x)
3: =(a-5)^2-4b^2
=(a-5-2b)(a-5+2b)
5: =x^2-mx-nx+mn
=x(x-m)-n(x-m)
=(x-m)(x-n)
6: =(4a^2-3a-18-4a^2-3a)(4a^2-3a-18+4a^2+3a)
=(-6a-18)(8a^2-18)
=-6(2a-3)(2x+3)(a+3)
\(1,x^3-x=x\left(x^2-1\right)=x\left(x^2-1^2\right)=x\left(x-1\right)\left(x+1\right)\)
\(2,4ax^3-ax=ax\left(4x^2-1\right)=ax\left[\left(2x\right)^2-1^2\right]\) \(=ax\left(2x-1\right)\left(2x+1\right)\)
\(3,x^3-2x^2+x\)
\(=x^3-x^2-x^2+x\)
\(=\left(x^3-x^2\right)-\left(x^2-x\right)\)
\(=x^2\left(x-1\right)-x\left(x-1\right)\)
\(=\left(x-1\right)\left(x^2-x\right)=\left(x-1\right).x\left(x-1\right)=x\left(x-1\right)^2\)
\(4,y-4xy+4x^2y\)
\(=y\left(1-4x+4x^2\right)\)
\(=y\left(1^2-2.1.2x+\left(2x\right)^2\right)^{ }\)
\(=y\left(1-2x\right)^2\)
a, \(\left(x^3-1\right):\left(x-1\right)=x^2+x+1\)
b, \(\left(x^2-2x+4\right)\left(x+2\right)=x^3+8\)
\(c,x^2-4=\left(x-2\right)\left(x+2\right)\)
a) (a2 - 1)3- ( a4 + a2+1)(a2-1)
= (a2 - 1)3 - (a2 - 1)3 =0
b) (a4 - 3a2+ 9)(a2+3) - (3+a2)3
= (3+a2)3 - (3+a2)3
=0